ECG In Smartwatches and Smart Bracelets: Can They Be Trusted? (The Peerian Journal, 2026)
In recent years, wearable technologies, particularly smartwatches and smart bracelets, have become increasingly popular tools for monitoring human health. The integration of electrocardiography (ECG) functions into consumer wearable devices has significantly expanded the possibilities of digital healthcare and preventive cardiology. This article investigates the biophysical principles of ECG signal acquisition in wearable devices and analyzes the reliability of ECG measurements across different smartwatch brands, including Apple, Samsung, Huawei, Garmin, Amazfit, and Withings. The study evaluates diagnostic accuracy, signal quality, sensitivity, specificity, and clinical limitations of wearable ECG systems. The findings indicate that although modern smartwatches demonstrate high accuracy in detecting atrial fibrillation and basic rhythm disorders, substantial differences exist among brands due to sensor quality, algorithms, filtering methods, and data interpretation systems. Smartwatch ECG technologies show strong potential as auxiliary monitoring tools but cannot fully replace conventional 12-lead clinical ECG systems.